Polyclonal emergence of vanA vancomycin-resistant Enterococcus faecium in Australia. (24th December 2016) - van Hal, Sebastiaan J.; Espedido, Björn A.; Coombs, Geoffrey W.; Howden, Benjamin P.; Korman, Tony M.; Nimmo, Graeme R.; Gosbell, Iain B.; Jensen, Slade O.
Abstract : Objectives: To investigate the genetic context associated with the emergence of vanA VRE in Australia. Methods: The whole genomes of 18 randomly selected vanA -positive Enterococcus faecium patient isolates, collected between 2011 and 2013 from hospitals in four Australian capitals, were sequenced and analysed. Results: In silico typing and transposon/plasmid assembly revealed that the sequenced isolates represented (in most cases) different hospital-adapted STs and were associated with a variety of different Tn 1546 variants and plasmid backbone structures. Conclusions: The recent emergence of vanA VRE in Australia was polyclonal and not associated with the dissemination of a single 'dominant' ST or vanA -encoding plasmid. Interestingly, the factors contributing to this epidemiological change are not known and future studies may need to consider investigation of potential community sources.